PERTANGGUNGJAWABAN PIDANA WARGA NEGARA ASING PELAKU KAWIN KONTRAK DITINJAU DARI ASPEK KEJAHATAN PERDAGANGAN ORANG : Studi Kasus Putusan No.924/pid.sus/2019/PN.Ptk - Elvini Tiara Putri, (2021)
The criminal act of trafficking in persons develops in various ways, through the pretext of contract marriage with foreign nationals which is ultimately abused by the parties involved. aims to minimize the Crime of Trafficking persons in Indonesia. The formulation of the problems to be discussed is related to how criminal responsibility of foreign citizens and how the elements of proof of the Crime of Trafficking Persons in case Number 924./PID.SUS/2019/PN.ptk These it type of research is normative juridical in form of descriptive analysis, with a problem approach in the form of a case approach. data comes from primary and secondary legal materials. Data collection used a comparison technique between literature studies and previous research. Contract marriage is not included in the Marriage regulation and the rules governing the crime of trafficking in persons. State law does not recognize contract marriages, it is difficult to classify them. Perpetrators can be prosecuted with the law that regulates the Crime of Trafficking in Persons and the rules on Immigration, which contain almost the same elements but if the qualifications are wrong because they do not meet the elements, then the victim will feel disadvantaged.